The relationship of learning motivation and higher-order thinking skills with students scientific literacy ability - Yusril Haq Ismail; Firdaus Daud; Rachmawaty Rachmawaty (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Scientific literacy is a key 21st-century competency that students must possess. However, assessment results show Indonesian students’ science literacy remains low. This study aims to determine the relationship between learning motivation and higher-order thinking skills (HOTS) toward students’ scientific literacy. A quantitative approach with an ex post facto design was used. The sample consisted of 350 twelfth-grade science students selected through cluster random sampling from four public high schools in Maros Regency. Instruments included a learning motivation questionnaire, a HOTS test, and a scientific literacy test. Results showed average scores for learning motivation (67.41), HOTS (64.29), and scientific literacy (66.70), all in the moderate category. Correlation analysis revealed significant relationships between learning motivation (r = 0.626) and HOTS (r = 0.430) with scientific literacy. Simultaneously, both variables contributed 22.6% to science literacy (R² = 0.226; sig. = 0.00). These findings emphasize the importance of integrating affective and cognitive aspects to improve students’ scientific literacy in science education. It is recommended that efforts to improve science literacy focus on strengthening students' affective and cognitive aspects through contextual, project-based, and inquiry-based learning approaches that are relevant to real life. Abstrak. Literasi sains merupakan kompetensi penting abad ke-21 yang harus dimiliki peserta didik. Namun, hasil asesmen menunjukkan tingkat literasi sains siswa Indonesia masih rendah. Tujuan studi ini adalah untuk mengetahui hubungan antara motivasi belajar dan keterampilan berpikir tingkat tinggi terhadap literasi sains peserta didik SMA. Penelitian menggunakan pendekatan kuantitatif dengan desain ex post facto. Sampel terdiri dari 350 siswa kelas XII IPA yang dipilih secara cluster random sampling dari empat SMA di Kabupaten Maros. Instrumen berupa angket motivasi belajar, tes HOTS, dan tes literasi sains. Hasil menunjukkan nilai rata-rata motivasi belajar sebesar 67,41, HOTS sebesar 64,29, dan literasi sains sebesar 66,70 (kategori sedang). Uji korelasi menunjukkan motivasi belajar berhubungan signifikan dengan literasi sains (r = 0,626), demikian pula HOTS (r = 0,430). Secara simultan, kontribusi kedua variabel terhadap literasi sains sebesar 22,6% (R² = 0,226; sig. = 0,00). Temuan menekankan pentingnya penguatan aspek afektif dan kognitif dalam pembelajaran untuk meningkatkan literasi sains. Direkomendasikan upaya peningkatan literasi sains difokuskan pada penguatan aspek afektif dan kognitif siswa melalui pendekatan pembelajaran kontekstual, berbasis proyek, dan inkuiri yang relevan dengan kehidupan nyata.